Kontribusi Kompetensi Pedagogik Guru Terhadap Motivasi Belajar Siswa - Siti Nuraeni Mitra; Kun Nurachadijat (Lembaga Pengembangan Kinerja Dosen, 2023)
This article discusses the Influence of Pedagogic Competence on Student Learning Motivation, namely where an ability to understand the characteristics of students, in mastering theories, models and learning methods, learning principles, design, implementation of learning, evaluating learning outcomes and following up on them. As well as the ability to develop students to actualize the various potentials they have. Learning Motivation to encourage, stimulate, or move someone to perform an action or activity with the aim of achieving the desired learning outcomes. This study uses a qualitative descriptive analysis approach through library research which is a review of concepts and content (content analysis). The results of this study are that teacher's Pedagogic Competence in managing learning needs attention. A teacher's competence will be maximized and the learning process will run smoothly if supported by learning facilities in teaching and learning activities. and will affect the High and Low Student Learning Motivation.